Strategic Information Systems / A European Perspective - Ciborra Claudio; Jelassi Tawfik (John Wiley & Sons, 1995)
This book discusses the most recent methodologies of SIS applications and presents a wide range of SIS case studies with examples, both successful and unsuccessful, that relate to efforts in Europe. Preface, Conceptual Papers, The Grassroots of IT and Strategy, Information Systems Planning at the Corporate Level, Knowledge as Strategy: Reflections on Skandia International and Shorko Films, Establishing a National Information Technology Infrastructure: The Case of the French Videotex System, Shorko Films S.A, BP Chemicals' Commercial System: A Strategic Transition, BP Chemicals' Commercial System: Historical Supplement to the Case on IT Risk and Project Management, BP Chemicals' Commercial System: IT Risk and Project Management, Skandia International, The Union Bank of Finland, Insurance Inc.: A Case from the Finnish Insurance Industry, MSAS Cargo International: Global Freight Management, Index.